2023
DOI: 10.1101/2023.05.24.542018
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of mitoribosome reveals mechanism of mRNA binding, tRNA interactions with L1 stalk, roles of cofactors and rRNA modifications

Abstract: The mitoribosome translates mitochondrial mRNAs and regulates energy conversion that is a signature of aerobic life forms. We present a 2.2 A resolution structure of human mitoribosome together with validated mitoribosomal RNA (rRNA) modifications, including aminoacylated CP-tRNAVal. The structure shows how mitoribosomal proteins stabilise binding of mRNA and tRNA helping to align it in the decoding center, whereas the GDP-bound mS29 stabilizes intersubunit communication. Comparison between different states, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 116 publications
(147 reference statements)
0
6
0
Order By: Relevance
“…These conformational changes are accompanied by a downward shift of helix 71 (~ 4-5 Å) as compared to the untreated monosome (Fig. 4B) 32 . Additionally, nucleotide C2603 ips inward together with A2600, with which it forms stacking interactions (Fig.…”
Section: Fig S4b)mentioning
confidence: 85%
See 1 more Smart Citation
“…These conformational changes are accompanied by a downward shift of helix 71 (~ 4-5 Å) as compared to the untreated monosome (Fig. 4B) 32 . Additionally, nucleotide C2603 ips inward together with A2600, with which it forms stacking interactions (Fig.…”
Section: Fig S4b)mentioning
confidence: 85%
“…Tigecycline occupies the PTC, with its 9-t-butylglycylamido substituent stretching adjacent to the P-tRNA (green), and the A ring interacting with the mL45 N-terminal extension (pink). Upon tigecycline binding, A2725 nucleobase shifts and stacks against ring D in both the P-tRNA only and the A-(blue), P-tRNA mitoribosomal classes, as compared to the untreated (tigecycline) mitoribosome (PDB:7QI4 32 ). G2992, U2993, and G3063 in the PTC rearranges upon binding of the A-tRNA (as also observed for the untreated mitoribosomes).…”
Section: Tigecycline Binds To the Peptidyl Transferase Center Of The ...mentioning
confidence: 99%
“…In humans, mitochondrial translation sometimes starts with AUA or AUU instead of AUG. Recent structural study focusing on the mt-rRNA modifications within the mitoribosome, demonstrated that the m 4 C1486 interacts with the phosphate group of the last nucleotide in the P-site mRNA codon via hydrogen bonding [ 30 ]. Speculatively, m 4 C1486 methylation may refine the P-site’s structure, impacting on decoding accuracy for these codons, but its importance needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, RNA19 has been shown to bind PTCD1, a protein required for 16S mt-rRNA maturation and ribosome assembly [ 32 ]. Indeed, from the inspection of the most recent 3D structure of the human mitoribosome at 2.2 Å resolution [ 33 ], the hypothetical ‘tail’ of RNA19 (consisting of mt-tRNALeu UUR and mt-ND1 mRNA) would protrude from the surface of the mt-LSU in close proximity to uL3m, bL17m and mL39 ( Figure S5 ). The latter, together with mL45, is part of a protein layer that surrounds the polypeptide exit site; it shows homology with RNA-binding proteins whose regions for RNA binding are oriented towards the solvent and not used for interaction with rRNA [ 34 ].…”
Section: Discussionmentioning
confidence: 99%